Combined Experimental and Computational Methods Reveal the Evolution of Buried Interfaces during Synthesis of Ferroelectric Thin Films. Issue 10 (1st June 2015) - Jones, Jacob L.; LeBeau, James M.; Nikkel, Jason; Oni, Adedapo A.; Dycus, J. Houston; Cozzan, Clayton; Lin, Fang‐Yin; Chernatynskiy, Aleksandr; Nino, Juan C.; Sinnott, Susan B.; Mhin, Sungwook; Brennecka, Geoff L.; et al.
<x xml:space="preserve">Abstract</x> Understanding interfaces between dissimilar materials is crucial to the development of modern technologies, for example, semiconductor–dielectric and thermoelectric–semiconductor interfaces in emerging electronic devices. However, the structural characterization of buried interfaces is challenging because many measurement techniques are surface sensitive by design. When interested in interface evolution during synthesis, the experimental challenges multiply and often necessitate in situ techniques. For solution‐derived lead zirconate titanate (PZT) ferroelectric thin films, the evolution of buried interfaces during synthesis (including dielectric–metal and metal–metal) is thought to dramatically influence the resultant dielectric and ferroelectric properties. In the present work, multiple experimental and computational methods are combined to characterize interface evolution during synthesis of ferroelectric PZT films on platinized Si wafers—including in situ X‐ray diffraction during thermal treatment, aberration‐corrected scanning transmission electron microscopy of samples quenched from various synthesis states, and calculations using density functional theory. Substantial interactions at buried interfaces in the PZT/Pt/Ti/SiOx/Si heterostructure are observed and discussed relative to their role(s) in the synthesis process. The results prove that perovskite PZT nucleates directly from the platinum (111)‐oriented bottom electrode and reveal the roles of Pb and O diffusion and intermetallic Pt3Pb and Pt3Ti phases.